Mitigation, Avoidance, or Acceptance? Managing Supplier Sustainability Risk. Issue 2 (20th December 2015) - Hajmohammad, Sara; Vachon, Stephan
Abstract : This study takes a conceptual theory building approach to develop a framework for managing supplier sustainability risk—the adverse impact on a buying organization from a supplier's social or environmental misconduct. Using anecdotal evidence and the literature, we present four distinct risk management strategies that supply managers adopt: risk avoidance, monitoring‐based risk mitigation, collaboration‐based risk mitigation, and risk acceptance. Drawing on agency and resource dependence theories, we study how the interactions of two key risk management predictors—that is, the supply managers' perceived risk and the buyer–supplier dependence structure—affect supply managers' strategy choice. Specifically, we propose that a collaborative‐based mitigation strategy, involving direct interaction and solution development with the suppliers, is selected by supply managers in a high perceived risk‐buyer dominant context. In a low perceived risk‐buyer dominant context, however, a monitoring‐based mitigation strategy is preferred. When the buyer and the supplier are not dependent on each other and there is a low perceived risk, the supply managers accept the risk by taking no actions, whereas in a high perceived risk‐independent context the supply managers would avoid the risk by terminating the relationship with the supplier. We conclude the study by describing the theoretical contributions and managerial implications of the study as well as the avenues for future research.